Advancing Medical Education in a Mental Health Trust: Trainees’ and Students’ Perspectives – Focus Groups - Michelle Keag; Varoonan Sritharan; Bruce Tamilson (BJPsych Open, 2025)
Aims: Medical education is a cornerstone of the NHS, influencing the continuous improvement of patient care. This study aims to explore the experiences of psychiatric trainees and medical students within a mental health trust, identifying opportunities to enhance medical education quality.